AN ANALYSIS OF RELIGION BIAS IN ENGLISH COURSEBOOK OF HIGHSCHOOL STUDENT ISSUED BY INDONESIAN GOVERNMENT - Sanjani, Muhammad Iqwan (PEOPLE: International Journal of Social Sciences, 2015)
The demand of English as a global language has become the most popular issue in ESL world. It results to the growing demand of English coursebook to assist student accelerating their competence. It is therefore the presence of a coursebook in teaching and learning process is fundamentally important. As well as the massive number of coursebooks, the analysis towards its contents is believed to be an urgent conduct among educators. However this analysis has rarely been practised today. Most importantly to the external factor sourrounding the process of coursebook design in which the coursebook is made such as religion, gender and culture. It is due to the fact that the process of coursebook writing is always be adjusted to the local culture or religion where the coursebook is used. Hence, this research will further assess the religion bias as appeared in student’s english coursebook. The researcher has analyzed five english coursebooks issued by the Indonesian government in which the researcher performs literature study and observation to attain the result. After collecting the data, researcher uses critical discourse analysis to further process the data. The research suggests that there is a huge tendency of bias in every coursebook that tends to expose the practice of certain religion group in Indonesia. This research will be a good reference where coursebook writers or designers could create a coursebook that is free from any bias. Further, it could maintain fairness in education without any bias to certain community or group only.